For a New Dawn. Notes on the End of the World among the I’kʉ People of the Sierra Nevada de Santa Marta (Colombia) - Arenas Gómez, Jose (Revista Española de Antropología Americana, 2025)
In this article, I explore the notion of cataclysm among the Indigenous groups of the Sierra Nevada de Santa Marta, with a particular focus on my experience with the I’kʉ people. I examine how origin narratives and ritual practices express a constant concern about the end of the world, associated with cataclysms such as the great flood or the sun’s imbalance. I illustrate that, within the Sierra´s cosmos, each ending seems to be also the beginning of a new cycle. Here, ritual practices aim to restore an ever-fragile equilibrium through dynamics of reciprocity and commensality that strengthen bonds of familiarization among beings and prevent chaos.